Еconomic security of construction enterprises under conditions of economic cyclicality: the role of financial stability and anti-crisis potential - Lysytsia, N; Horbenko, S (Ways to Improve Construction Efficiency, 2025)
The article examines the theoretical and applied foundations of ensuring the economic security of construction enterprises under conditions of economic cyclicality. It is determined that the current operating environment of enterprises is characterized by a high level of uncertainty, dynamic external conditions, and the intensification of crisis phenomena, which become especially acute during economic downturns. It is substantiated that cyclical fluctuations in the economy significantly affect the performance of enterprises, leading to a decline in their solvency, liquidity, financial stability, and investment attractiveness, thereby increasing the level of threats to economic security. The essence of economic security of an enterprise is clarified as a complex and dynamic characteristic that reflects its ability to resist internal and external threats, ensure efficient use of resources, and adapt to changes in economic conditions across different phases of the economic cycle. It is proven that one of the key factors in ensuring economic security is the financial stability of the enterprise, which serves as the basis for maintaining liquidity, solvency, financial equilibrium, and the ability to recover under crisis conditions. Special attention is paid to the anti-crisis potential as an integral component of the enterprise’s economic security system. It is established that anti-crisis potential characterizes the ability of an enterprise to timely identify risks and threats, assess their impact, and develop effective managerial decisions aimed at their neutralization or minimization. The peculiarities of forming anti-crisis potential depending on the stage of the enterprise life cycle are considered, and it is substantiated that different sources of threats to economic security dominate at different stages of development, which necessitates the use of appropriate anti-crisis management tools. It is determined that effective ensuring of the economic security of construction enterprises under conditions of economic cyclicality is possible only through the integrated combination of financial stability management mechanisms and the development of anti-crisis potential. This approach enhances the adaptability of enterprises to changes in the external environment, minimizes the negative impact of economic downturns, ensures continuity of operations, and creates the basis for long-term development and strengthening of competitive positions in the market.